Preparation of metal oxide supported catalysts and their utilization for understanding the effect of a support on the catalytic activity - Seth, Jhumur; Dubey, Prashant; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2018)
A convenient way of anchoring transition metal nanoparticles (palladium, platinum, rhodium and ruthenium) onto metal oxide supports (magnesium oxide and zirconium oxide) by means of a modified sol-gel technique is demonstrated. Use of toluene dispersed, ligand protected pre-synthesized nanoparticles during sol-gel synthesis delivered size-controlled, spatially distributed, well-adhered transition metal nanoparticles (MNPs) on metal oxide supports. The catalytic activities of these supported nanoparticles were tested for the p-nitro phenol reduction reaction. It was observed that the reaction kinetics were crucially dependent on the catalyst support and MNP size. The influence of the magnesium oxide and zirconium oxide supports towards the catalytic performance of the anchored transition MNPs was probed using cyclic voltammetry and the differences in the same were attributed to the support-induced modification in the electronic properties of the MNPs. Our results indicated that magnesium oxide is a better support than zirconium oxide.

Water-assisted stability of carbene: cyclic voltammetric investigation of 1-ethyl-3-methylimidazolium ethylsulfate ionic liquid - Jain, Preeti; Chaudhari, Vijay R.; Kumar, Anil (Physical Chemistry Chemical Physics, 2019)
In this work, we report electrochemical studies on imidazolium-based ionic liquids with an objective to explore the possibility of carbene formation in their dilute aqueous solutions. Conventionally, water plays a detrimental role during investigations involving ionic liquids, and this role has been investigated via electrochemical studies in aqueous ionic liquid solutions. There are varying opinions regarding the influence of water on the physicochemical behaviour of ionic liquids that require an in-depth understanding. To eludicate the role of water, we attempted to evaluate the electrochemical performance of ionic liquids in water as a solvent, and the influence of water on ionic liquids was explored through feasibility and stability studies on carbene formed in an aqueous imidazolium-based ionic liquid solution. The electrochemical investigation of an aqueous solution of 1-ethyl-3-methylimidazolium ethylsulfate ([EMIM][EtSO4]) revealed a redox couple. Detailed investigations suggest that reduction of the imidazolium cation occurs at the C2 position, with subsequent formation of carbene. Furthermore, an anodic peak was found to be associated with the oxidation of carbene. The coulometric process associated with the anodic peaks indicated that the two-electron oxidation of carbene occurred. The stability of carbene in water was evaluated through the use of different protic and aprotic solvents. The hydrogen bond-forming ability of carbene with water seems to be responsible for its improved stability in water.

Mechanistic aspects of methanol electro-oxidation reaction through cyclic voltammetry: is it correct to blame carbon monoxide for catalyst poisoning? - Deshpande, Pooja S.; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (Energy Technology, 2020)
The mechanism of the methanol oxidation reaction is revisited using systematic cyclic voltammetric studies. These studies clearly indicate that the peak during the cathodic scan belongs mainly to electro-oxidation of the carbon monoxide, and that only a fraction of this carbon monoxide remains adsorbed on the electrode, contrary to what previous reports suggested. More details can be found in article number by Bhagavatula L. V. Prasad and co-workers.
Keywords: carbon monoxide; cyclic voltammetry; electrocatalysts; electrode poisoning; Methanol oxidation